(untitled) (Global Journals of Research in Engineering, 2012)
The aluminium stiffener panels in ship structure are paramount to ensure safety and to guarantee the structural strength and integrity of the ship. The aluminium stiffener panel is very important to ship building, especially when the ship faces collision or unstabilized structure; the aluminium stiffener panel tends to increase bending moment, vertical shear force and stresses. This study investigate the strength of the aluminium stiffener panel at the amidship bulkhead with different shapes and typesin order to determine the strength of the aluminium stiffener from its features. AA 5083-H116 aluminium stiffener panel used has been approved by the recognized organization for shipbuilding. The aluminium stiffener panel has been tested using bending moment test and compressive load to obtain the highest endurance. Three types of aluminium stiffener panels, which are a flat shaped, L-shaped and T-shaped panel, are used in order to obtain the best panel ability for a better ship structural system. The aluminium stiffener panel is tested at the area where it is different to determine area where they are affected by extreme heat due to the welding results and fabrication. The result has showed that the aluminium stiffener panel in shipbuilding process effect in an area without extreme heat is more stable.